Terminalia bellirica fruit extracts: in-vitro antibacterial activity against selected multidrug-resistant bacteria, radical scavenging activity and cytotoxicity study on BHK-21 cells - M. Priyanga Jayamal Dharmaratne; Amirthasingam Manoraj; Vasanthi Thevanesam; Asela Ekanayake; Nimal Savitri Kumar; Veranja Liyanapathirana; Eranga Abeyratne; B. M. Ratnayake Bandara (BMC, 2018)
Abstract Background Identification of novel sources for developing new antibiotics is imperative with the emergence of antibiotic resistant bacteria. The fruits of Terminalia bellirica (Gaertn) Roxb., widely used in traditional medicine, were evaluated for antibacterial activity against multidrug-resistant (MDR) bacteria, antioxidant activity and cytotoxicity. Methods Twelve solvent extracts of T. bellirica fruits were prepared by direct aqueous extraction and sequential extraction with dichloromethane, methanol and water using Soxhlet, bottle-shaker and ultrasound sonicator methods. Antibacterial activity of the extracts was tested against 16 strains MDR bacteria-methicillin-resistant Staphylococcus aureus (MRSA), extended spectrum β-lactamase (ESBL) producing Escherichia coli and MDR Acinetobacter spp., Klebsiella pneumoniae and Pseudomonas aeruginosa-and 4 control organisms, using the cut-well diffusion method. The minimum inhibitory concentration (MIC) was determined using an agar dilution method. The radical scavenging activity of six antibacterial extracts was screened against 2,2'-diphenyl-2-picrylhydrazyl (DPPH) and correlation was established between EC50 (50% effective concentration) values and the total phenolic content (TPC). Cytotoxicity was determined for the most potent antibacterial extract on baby hamster kidney (BHK-21) cells by Tryphan Blue exclusion method. Statistical analysis was carried out by one-way analysis of variance at significant level p < 0.05 using "SigmaPlot 10" and "R 3.2.0" software. Results All aqueous and methanol extracts displayed antibacterial activity (MIC 0.25-4 mg/mL) against all strains of MRSA, MDR Acinetobacter spp. and MDR P. aeruginosa. The sequential aqueous extracts (MIC, 4 mg/mL) inhibited ESBL producing-E. coli. None of the extracts exhibited activity against MDR K. pneumoniae (MIC > 5 mg/mL). The sequential methanol extract (Soxhlet) recorded high antibacterial activity and the highest DPPH radical scavenging activity (EC50, 6.99 ± 0.15 ppm) and TPC content (188.71 ± 2.12 GAE mg/g). The IC50 (50% inhibition concentration) values of the most potent antibacterial extract-the direct aqueous extract from reflux method-on BHK-21 cells were 2.62 ± 0.06 and 1.45 ± 0.08 mg/ml with 24 and 48 h exposure, respectively. Conclusions Results indicate that T. bellirica fruit is a potential source for developing broad-spectrum antibacterial drugs against MDR bacteria, which are non-toxic to mammalian cells and impart health benefits by high antioxidant activity.